2001
DOI: 10.2337/diabetes.50.10.2349
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Ingestion Decreases Glucose Disposal During a Hyperinsulinemic-Euglycemic Clamp in Sedentary Humans

Abstract: The purpose of this investigation was to examine the effect of caffeine (an adenosine receptor antagonist) on whole-body insulin-mediated glucose disposal in resting humans. We hypothesized that glucose disposal would be lower after the administration of caffeine compared with placebo. Healthy, lean, sedentary (n ‫؍‬ 9) men underwent two trial sessions, one after caffeine administration (5 mg/kg body wt) and one after placebo administration (dextrose) in a double-blind randomized design. Glucose disposal was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
133
4
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(158 citation statements)
references
References 42 publications
(48 reference statements)
14
133
4
5
Order By: Relevance
“…Ingestion of caffeine at a dose equivalent to drinking 3-4 cups of coffee decreased whole-body glucose disposal by 30%, in agreement with our previous report (22) (Fig. 1).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Ingestion of caffeine at a dose equivalent to drinking 3-4 cups of coffee decreased whole-body glucose disposal by 30%, in agreement with our previous report (22) (Fig. 1).…”
Section: Discussionsupporting
confidence: 82%
“…In rat adipocytes (20) and in the perfused contracting rat hindlimb (21), methylxanthines inhibited insulin-stimulated glucose uptake, and this inhibitory action was attributed to the antagonistic effects of methylxanthine on the A 1 adenosine receptor. We have previously shown that caffeine administration at doses eliciting plasma concentrations equivalent to concentrations obtainable after drinking 3-4 cups of coffee (19) decreased whole-body insulin sensitivity in sedentary males (22). However, it is not known whether the reduction in whole-body glucose disposal after caffeine ingestion resulted from diminished glucose uptake in skeletal muscle.…”
mentioning
confidence: 99%
“…Coffee and tea consumption may affect serum uric acid levels via various mechanisms including influence on insulin resistance (2)(3)(4)(5)(6)(7)(8)(9), but few data are available. Only 1 cross-sectional study investigated the link between these beverages and serum uric acid level based on 2,240 Japanese men and found a significant inverse association between coffee consumption and serum uric acid levels but no association with tea consumption (10).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, short-term studies have consistently shown that acute administration of caffeine induces insulin resistance and impairs glucose tolerance (3,5,6). Longterm effects of caffeine and other components of coffee, which may be more relevant on insulin secretion, have been less well studied.…”
mentioning
confidence: 97%